Correction: Recovering lost customers (2015, Vol. 3, No. 2, p. 25-40) - Senić, Radoslav; Milojević, Sonja (Hotel and Tourism Management, 2017)
Correction: Recovering lost customers (2015, Vol. 3, No. 2, p. 25-40)